Ammonothermal Synthesis and Crystal Structure of the Nitridoalumogermanate Ca1–xLixAl1–xGe1+xN3 (x ≈ 0.2). Issue 6 (5th February 2018) - Häusler, Jonas; Eisenburger, Lucien; Oeckler, Oliver; Schnick, Wolfgang
Abstract : The new nitridoalumogermanate Ca1– x Li x Al1– x Ge1+ x N3 ( x ≈ 0.2) was synthesized from supercritical ammonia at 925 K and 185 MPa starting from the intermetallic precursor Ca3 Al2 Ge2 and Li as mineralizer. The crystal structure was refined by the Rietveld method; Ca1– x Li x Al1– x Ge1+ x N3 with x ≈ 0.2 [ a = 9.9822(5), b = 5.7763(2), c = 5.1484(1) Å, Z = 4, Rwp = 0.0492] crystallizes in orthorhombic space group Cmc 21 (no. 36). Needle‐shaped crystals with up to 15 µm in length were detected by scanning electron microscopy. Possible cation ordering was analyzed by transmission electron microscopy. No superstructure reflections were observed in electron diffraction patterns and the structure model was confirmed by Z‐contrast imaging. The composition was verified by energy‐dispersive X‐ray spectroscopy on single crystals and inductively coupled plasma optical emission spectrometry. Optical properties were studied by diffuse reflectance spectroscopy, showing a broad absorption band between 250 and 300 nm. The optical band gap was estimated to be 4.3 eV at room temperature using the Tauc method. Abstract : The first nitridoalumogermanate Ca1– x Li x Al1– x Ge1+ x N3 ( x ≈ 0.2) was synthesized under ammonothermal conditions. This nitride crystallizes in a superstructure derived from the wurtzite type and can be regarded as a solid solution of LiGe2 N3 and hypothetical CaAlGeN3 . SAED and STEM‐HAADF were carried out to investigate possible ordering phenomena.